Cinnamaldehyde Inhibits the Function of Osteosarcoma by Suppressing the Wnt/β-Catenin and PI3K/Akt Signaling Pathways [Retraction] - Huang Y; Chen J; Yang S; Tan T; Wang N; Wang Y; Zhang L; Yang C; Huang H; Luo J; Luo X (Dove Medical Press, 2024)
Huang Y, Chen J, Yang S, et al. Drug Des Devel Ther. 2020;14:4625–4637. We, the Editor and Publisher of the journal Drug Design, Development and Therapy, have retracted the following article. Following publication of the article, concerns were raised about the duplication of images from Figures 4 and 6. Specifically, Images for Figure 4F, MG63, control and 80 µM, have been duplicated. Images for Figure 4J, MG63, 12H, control and 100 µM, have been duplicated. Images for Figure 6D, Osteosarcoma, Blank (x 200) and 75 mg/kg (x 200) have been duplicated. Images for Figure 6E, p-Akt (Ser473), 50 mg/kg (x 400) and 75 mg/kg (x 400) have been duplicated. The authors responded to our queries but were unable to provide a satisfactory explanation for the duplicated images or provide satisfactory data for the study. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article and the authors were notified of this. We have been informed in our decision-making by our editorial policies and COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.